Distribution and characterization of microplastics in beach sand from three different Indian coastal environments. (March 2019) - Tiwari, M.; Rathod, T.D.; Ajmal, P.Y.; Bhangare, R.C.; Sahu, S.K.
Abstract: The occurrence of microplastic particles were evaluated on beaches along the Indian coast from three different locations Girgaon Mumbai (Arabian sea coast), Tuticorin, and Dhanushkodi (Bay of Bengal coast). Density separation method was adopted for isolation of microplastics from sand. Isolated microplastics were characterized using three different analytical techniques e.g. fluorescence microscopy (after staining with Nile Red), FTIR and SEM-EDS techniques. Microplastic concentrations in beach sands were from 45 ± 12 # MP kg −1 to 220 ± 50 # MP kg −1 of dry sand. The order of abundance of plastic type was polyethylene (43%) > polyethylene terephthalate (17.3%) ≈ polystyrene (17%) > polypropylene (12.3%) > Others (11%) > polyvinylchloride (1.33%), and very similar profile was observed for all monitored locations. SEM images show microplastics surfaces with characteristic cracks, suggests their polymer aging, mechanical and oxidative weathering, which was found highest for the microplastics collected from Mumbai. Graphical abstract: Unlabelled Image Highlights: The order of total microplastic abundance in beach sands was megacity, industrial city followed by religious and tourist city Fibrous shapes microplastics were observed with the majority compared to granule shape, films. Polyethylene and polystyrene microplastics were found in dominantly in beach sand samples. SEM images of microplastics surfaces indicates their aging, mechanical and oxidative weathering.